Productivity, competition and economics of intercropping legumes in finger millet (Eleusine coracana) at different fertility levels - MAITRA, S; GHOSH, D C; SOUNDA, G; JANA, P K; ROY, D K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1994 - 95 at Birbhum (West Bengal) to study the performances of inter cropping legumes in finger millet at different fertility levels, The results indicated that intercropping red gram (Cajanus cajan L. Millsp.) and groundnut (Arachis /zypogaea L.) in finger millet (Eleusine coracana L. Gaertn.) gave higher total grain and straw yield compared to the sole cropping of finger millet under rainfed condition of upland (Ultisols) in lateritic belt of West Bengal. Intercropping pigconpea in finger millet increased land equivalent ratio, aggressivity, relative crowding coefficient and area time equivalent ratio. Legumes were more aggressive in intercropping system and tended to have depressing effect on finger millet. Intercropping of finger millet + pigeonpea and finger millet + groundnut showed higher net return and benefit: cost ratio. Application of 60-13.3-25 kg N-P-K/ha recorded maximum productivity and the highest net refurn followed by the application of 30-6.7-12.5 kg N-P-K/ha. However, the highest benefit/cost ratio was obtained from application of 30-6. 7-12.5 kg N-P-K/ha.